I73T mutation in the pulmonary surfactant protein C gene associated with pediatric interstitial lung disease a case study and the review of related literature - Huang, Li (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2014)
OBJECTIVE: To report a case of I73T mutation in the pulmonary surfactant protein (SP)-C gene associated with pediatric interstitial lung disease, and study the clinical diagnosis and review related literature, to investigate the role of gene detection in the diagnosis of interstitial lung disease in infants and children